Wykorzystanie metod taksonomicznych do budowy modeli zagregowanych - Gatnar, Eugeniusz (The Application of Cluster Analysis in Aggregation of Classifiers, 2007)
Combining multiple classifiers into an ensemble has proved to be very successful in the past decade. The key issue is the diversity of the component classifiers, because the most unrelated members the most accurate is the ensemble. In this paper we propose a new method of combining classifiers, that is based on clustering of the single models. We also compare different hierarchical clustering methods and diversity measures used to create the dissimilarity matrix.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 57-64